The Effect of Audit Quality, Financial Stability, and Audit Committee on Financial Statement Fraud (Case Study of Banking Companies Listed on the IDX in 2021-2023) - Dewi, Meylisa Kusuma; Wahyuni, Sri; Hariyanto, Eko; Winarni, Dwi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Audit Quality, Financial Stability, and Audit Committee on Financial Statement Fraud in banking sector companies listed on the Indonesia Stock Exchange (IDX). Financial statement fraud was measured using the Beneish M-Score method, categorized as a dummy variable. This study employed a quantitative approach and secondary data obtained from the companies' financial statements. The sampling technique used was purposive sampling, with a sample size of 31 companies meeting the criteria for the 2021-2023 period. Data analysis was performed using logistic regression using SPSS 23. The results of this study indicate that financial stability has a significant effect, while audit quality and the audit committee have no significant effect on financial statement fraud.